Investigating Visual Perception Problems and Visual Motor Skills Challenges in Adults with Low Vision and Healthy Controls Using TVMS-3. - Ekemiri, Dr.Kingsley; Deonath, Aniela; Chiemeke, Uche (Faculty of Medical Sciences, The UWI, St. Augustine Campus, Trinidad and Tobago, 2023)
Aim: To investigate visual perception problems and visual motor skills challenges in adults with Low Vision and healthy control using Test for Motor Visual Skills 3 (TVMS-3) Method: Data was obtained from both LV and non-LV patients through the administration of the Test for Visual Motor Skills (TVMS) at the UWI Clinic in the Couva Multi training facility. Prospective participants were identified through the Clinic's database, diabetes association vision screenings, and individuals meeting the inclusion criteria. LV patients were selected using the LV Clinic records and contacted via telephone. A questionnaire assessed demographic data and ocular health. 29 LV and 30 non-LV participants took part in the study. Result: The study analyzed responses from a total of 59 participants, including 29 LV individuals and 30 healthy controls. The LV group reported a higher likelihood of visual perception problems and ranked lower in percentiles on the TVMS-3 test. In terms of accuracy and error analysis, the control group performed better on the TVMS-3, with a higher mean score (X̄ = 35.48 ± 7.36) compared to the LV group (X̄ = 67.47 ± 8.21). Conversely, the LV group reported having more visual perception problems than the healthy control group. Conclusion: this research study revealed that adults with LV exhibited significantly poorer scores on the Test for Motor Visual Skills 3 (TVMS-3), indicating notable challenges in visual motor skills. Additionally, the LV group demonstrated a higher prevalence of visual perception problems compared to the healthy control group. These findings underscore the importance of targeted interventions and support to address visual motor skills and visual perception issues in individuals with LV. Further research is needed to develop effective strategies for intervention and rehabilitation in this population.